2020
DOI: 10.3389/fmed.2020.00332
|View full text |Cite
|
Sign up to set email alerts
|

Lung Involvement in Primary Sjögren's Syndrome—An Under-Diagnosed Entity

Abstract: Interstitial lung disease (ILD) represents a frequent extra-glandular manifestation of primary Sjögren's Syndrome (pSS). Limited published data regarding phenotyping and treatment exists. Advances in managing specific ILD phenotypes have not been comprehensively explored in patients with coexisting pSS. This retrospective study aimed to phenotype lung diseases occurring in a well-described pSS-ILD cohort and describe treatment course and outcomes. Between April 2018 and February 2020, all pSS patients attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
2
25
0
4
Order By: Relevance
“…Previous studies in pSS-ILD cohorts reported an average age at presentation ranging from 58 to 68 years, a female predominance, and a smoking history in 13%–31% of the patients, depending on the studied population. [ 2 3 4 6 7 8 10 23 24 ] In agreement with the cited studies, our cohort had a mean age at presentation of 60 years, 62% were women, and the majority were nonsmokers. Considerable variation among studies was noted regarding the prevalence of autoimmune symptoms and signs in pSS-ILD patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies in pSS-ILD cohorts reported an average age at presentation ranging from 58 to 68 years, a female predominance, and a smoking history in 13%–31% of the patients, depending on the studied population. [ 2 3 4 6 7 8 10 23 24 ] In agreement with the cited studies, our cohort had a mean age at presentation of 60 years, 62% were women, and the majority were nonsmokers. Considerable variation among studies was noted regarding the prevalence of autoimmune symptoms and signs in pSS-ILD patients.…”
Section: Discussionsupporting
confidence: 90%
“…[ 2 3 4 7 8 9 10 23 ] However, recent studies reported a higher prevalence of the UIP pattern, ranging between 42% and 92%, implying that significant heterogeneity occurs among pSS patients and among studied populations. [ 6 24 ] In the present study, UIP was the most common pattern, followed by NSIP. Regarding the serological test results, we showed that autoantibodies against SSA and SSB were positive in only 22% and 5% of the patients, respectively.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Case reports describing these treatments are limited. 37 Case reports on patients with CPFE show that they could possibly improve with lung volume reduction (LVR) in case of advanced emphysema, even without plethysmographic evidence of severe hyperinflation. 38 If LVR is not possible and after extensive exclusion of (lung) cancer, patients should be evaluated early for lung transplantation as the ultimate treatment modality of CPFE.…”
Section: Discussionmentioning
confidence: 99%